Materi Pendidikan Kewarganegaraan di Perguruan Tinggi dalam menghadapi tantangan era global - Tukiran Tukiran (Jurnal Cakrawala Pendidikan, 2006)
A Challenge for education in the ongoing era of globalization is the demand for qualityin human resources. Qualifiedhuman resources are thoese having a competent professionalism, acrativity in recognizing social gaps and finding their solutions, and a global view.The teaching materials in classes of Civic Education have tended to teach the students about the physical aspects of defending the country. The development of demoeratic values, social values of the society, awareness of law, and social disipline has not been the main purpose of the Civic Education class. The teaching method employed has also been the same as that of the class of Pancasila, of which the essence is indoctrination in the truthfulnes of Indonesia Ideology. Thes will only bring results in the cognitive sphere, and leave the aspects of attitude and behavior untouched